Cardiac Rehabilitation in Elderly Patients: Barriers and Strategies for Improvement - Atiq Ur Rehman; Faiz Ullah; Khan, Rahim Dil; Mahmood, Ijaz; Khan, Ajmal; Khan, Khushal (Indus Journal of Bioscience Research, 2025)
Introduction: Existing evidence shows cardiac rehabilitation (CR) significantly affects cardiovascular outcomes in elderly patients. Nevertheless, the involvement of people is still limited by numerous factors. This research reviews the hurdles that restrict older adults’ participation in Community Rehabilitation (CR) and examines ways of improving it. Objective: This paper aims to determine the factors that interfere with elderly patients’ engagement in CR and possible measures to enhance participation, compliance, and success. Materials and Method: This descriptive cross-sectional study was conducted from April, 2024 to September, 2024 at the Department of Cardiology, Hayatabad Medical Complex Peshawar, Pakistan. The data were obtained by administering a structured questionnaire to 120 elderly cardiac patients. Quantitative data were analyzed using a statistical package analysis system, while the qualitative responses were analyzed thematically. Results: The main challenges reported were inadequate knowledge (68%), transport problems (55%), and funding (48%). Patients mentioned in their ideas that home-based CR is 62% and better education is 58%. Conclusion: This study analyses potential solutions for overcoming logistical, financial, and educational challenges that might help increase CR uptake among elderly patients.